Sample preparation of circulating cell-free DNA by direct-on-specimen and silica-based methods - Ford, Andrew; Brown, Charmaine; Yeh, Chen- Hsiung (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Circulating cell-free DNA (cfDNA) in bloodstream of cancer patients have demonstrated tumor tissue-comparable genetic alterations, offering an unprecedented opportunity for longitudinal and real-time monitoring of highly dynamic tumor heterogeneity. However, the industry is currently using the silica-based cfDNA extraction method which is fundamentally flaw for unavoidable sample loss during binding, washing and elution steps. As a result, clinical cfDNA analysis requires large volume of blood owing to the poor extraction and recovery efficiency. To address these major challenges, we have developed and validated a proprietary direct-on-specimen (DOS) cfDNA enrichment technology. In this report, we set out to evaluate the analytical performance of cfDNA prepared in parallel by our method and the industry standard Qiagen kit.